The Impact of Authentic Leadership on Employee Engagement through Employee-Organization Relations - Ramadhan, Dyandra Armyta (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the influence of authentic leadership on employee engagement through employee and organizational relationships. Method: The sample used in this study was 85 employees of a telecommunications company in Surabaya. The analysis technique used in this study is Partial Least Square assisted by the use of the software SmartPLS3.0.  Results:  The results of this study indicate that authentic leadership has a significant positive effect on employee engagement, authentic leadership has a significant positive effect on employee-organization relationship, employee-organization relationship has a significant positive effect on employee engagement, and authentic leadership has a significant positive effect on employee engagement through employee-organization relationship. Novelty: The novelty of this study lies in its emphasis on the indirect effect of authentic leadership through employee-organization relationships, providing deeper insights into how leadership styles can foster employee engagement. These findings contribute to the existing body of knowledge on leadership and human resource management, offering practical implications for organizations aiming to improve employee commitment and motivation through effective leadership strategies.